A comparative study of nasal final prefixes in Malay and English - Sharifah Raihan Syed Jaafar, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This paper compares nasal final prefixes in Malay and English. In many languages, nasal and voiceless obstruent clusters are not allowed to emerge in the surface representation. Therefore, the clusters undergo some repair strategies, e.g. nasal assimilation, nasal deletion, nasalisation, nasal substitution, denasalisation and post-nasal voicing. This paper thus intends to investigate how the occurrence of clusters in Malay and English is resolved. Based on the data from previous studies, this paper shows that nasal and voiceless obstruent clusters are not entirely prohibited in Malay, as in /məŋ-komersil/ → [məŋ-komersil] ACT.PRF-commercial ‘to commercialise’, and are allowed to emerge in English as in /un-traditional/ → [un-traditional]. The occurrence of nasal and voiceless obstruent clusters in those words is due to the phonological characteristics of English and Malay, i.e. Uniform Exponence and lexical strata respectively. The occurrence of such cases in Malay and English could be explained satisfactorily by adopting a constraint-based theory named Optimality Theory (Prince and Smolensky, 1993). In the analysis, I demonstrated how Uniform Exponence and lexical strata were used to explain the case in hand.